Sistem Pendukung Keputusan Seleksi Calon Duta WisataKabupaten Sragen Dengan Metode Simple Additive Weighting - Setiawan, Bayu Cholid, Prof. Budi Murtiyasa, M. Kom (2017)
Tourism ambassador is a promoting media to introduce the local culture and the tourism potential that is belongs to each region. Tourism, Culture, Youth and Sport Service in Sragen hold a selection to choose the best male and female to be the tourism ambassador according to the requirements. The manual process make the selection become longer and less efficient. The evaluation process uses SPK is very helpful for judges in a selection process to get the best 10 male and 10 female from the number of enlister. This system uses Simple Additive Weighting (SAW) method that makes a weight ratio to the criterion first, then normalizes the matric table from the found criterion, and rank it to get the best alternative. The alternative here is the candidate of the tourism ambassador. This research is done to make a website-based system that can help judges in a selection process according to the definite criterion. The result of the research is a system application that support the result of the tourism ambassador candidate selection that uses SAW method in the calculation, so that it make easier for the judge in selection process. It is according to the criterion, fast, efficient, and fills the expectation.